2018
DOI: 10.1016/j.btre.2018.e00251
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and antibacterial effect of biosurfactant from Candida parapsilosis

Abstract: HighlightsThis is the first study which reports the ability of C. parapsilosis to produce biosurfactant. The organism was identified through morphology and sequencing studies. The biosurfactant was characterized and its potential antibacterial activity was explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 40 publications
5
34
0
1
Order By: Relevance
“…Other authors have evaluated the antimicrobial activity of biosurfactants, against P. aeruginosa and E. coli , produced by other microbial strains, different from Bacillus . For instance, Garg et al [27] showed that a biosurfactant extract produced from Candida parapsilosis was able to inhibit 58% of growth of E. coli at concentrations of 5 mg/mL as it can be observed in Table 1. Although it showed to be less effective than the biosurfactant extract obtained from CSW.…”
Section: Resultsmentioning
confidence: 99%
“…Other authors have evaluated the antimicrobial activity of biosurfactants, against P. aeruginosa and E. coli , produced by other microbial strains, different from Bacillus . For instance, Garg et al [27] showed that a biosurfactant extract produced from Candida parapsilosis was able to inhibit 58% of growth of E. coli at concentrations of 5 mg/mL as it can be observed in Table 1. Although it showed to be less effective than the biosurfactant extract obtained from CSW.…”
Section: Resultsmentioning
confidence: 99%
“…1 Presence of N−H stretch of amine group in biosurfactant was observed at 3,375.8 cm −1 in our previous report. 30 Various other functional groups such as O−H group, C=O bond stretching, and C=C were also observed. 30 Biosurfactant conjugated GQDs showed appearance of N−H stretch of CONH at 3,362.8 cm −1 .…”
Section: Ftirmentioning
confidence: 99%
“…30 Various other functional groups such as O−H group, C=O bond stretching, and C=C were also observed. 30 Biosurfactant conjugated GQDs showed appearance of N−H stretch of CONH at 3,362.8 cm −1 . Moreover, appearance of −C=O stretch of CONH of biosurfactant conjugated GQDs at 1,650.47 cm −1 (amide I) and 1,563.8 cm −1 (amide II) was observed, as shown in Figure 5.…”
Section: Ftirmentioning
confidence: 99%
See 1 more Smart Citation
“…The surfactant activity of these natural compounds is due to the existence of both hydrophilic and hydrophobic moieties in the molecular structure (Rane et al, 2017;López-Prieto et al, 2019). Biosurfactants have aroused considerable interest in recent decades due to their advantageous properties over synthetic surfactants, such as high selectivity and biodegradability, stability in a range of environmental conditions (temperature, pH, and salinity), and low toxicity, favoring their application in the recovery of hydrophobic compounds and as emulsifiers in the pharmaceutical, cosmetic, and food industries (Garg and Priyanka, 2018;Felix et al, 2018).…”
Section: Introductionmentioning
confidence: 99%